Proceed with Passion - Cummins, Paul F., 1937- (Book collections on Project MUSE., 2004)
Proceed With Passion: Engaging Students in Meaningful Education is filled with bold approaches to giving students the ingredients they most lack in their schooling a sense of purpose, a reason for wanting to learn and, ultimately, a passion to help others.